Austenitizing Behavior of Laser Solid Formed Ultrahigh‐Strength 300 M Steel. Issue 7 (8th February 2017) - Liu, Fenggang; Lin, Xin; Song, Menghua; Song, Kan; Wang, Feifan; Li, Qiuge; Han, Yifan; Huang, Weidong
Abstract : The influence of austenitizing treatment on the microstructure and mechanical properties of laser solid formed (LSFed) 300M steel is investigated within the austenitizing temperature range of 870–1050 °C. It is found that the dendritic segregation in 300M steel deposits (formed in the laser solid forming) gradually reduces with the increase of the austenitizing temperature, and even completely disappears when the austenitizing temperature reaches 1050 °C. Besides, the austenite grains and martensite packets in the LSFed 300M steel deposits changes little when the austenitizing temperature rises from 870 to 950 °C, but significantly coarsenes at the austenitizing temperature above 950 °C. The tensile test shows that the tensile strength of the samples reaches 2325 MPa after austenitizing heat treatment at 870 °C and, then, decreases slightly with the increase of the austenitizing temperature. For yields strength, it decreases slightly when the austenitizing temperature reaches 870–950 °C, while sharply decreases when the austenitizing temperature is above 950 °C. Moreover, a little effect of austenitizing temperature on the elongation and percentage reduction of area of the LSFed 300M steel is exhibited. Abstract : The microstructure of LSFed 300 M steel after austenitizing treatment is compared and discussed with the as‐deposited samples. Effect of austenitizing treatment on the microstructure and mechanical properties of laser solid formed 300M steel is studied. The strength of LSFed 300 M steel after austenitizing significantly increases and reaches the forgings standard.